Analisis Strategi Peningkatan Daya Kerja Central Processing Unit (CPU) Dalam Proses Pengolahan Data - Nur Zahra Maharani; Raihan Zacky Luthfi; Raga Amri; Raymond Erpindo Ginting (Journal Of Informatics And Busisnes, 2023)
The development of technology is growing rapidly both from performance, graphics, bandwidth and others so that a device with reliable capabilities is needed to help better performance, especially in the central processing unit. Data processing is a process of making data from original data into new data (information) in accordance with processing needs. This type of research method is qualitative where research is carried out in libraries through the collection of books, documents, archives, and other types. Basically, computer systems have several main functions, namely data processing, data storage, data movement, and control. In the context of data processing systems, the role of the Central Processing Unit (CPU) is very important in determining the performance of the entire system. This journal aims to analyze the various strategies that can be implemented to improve the workability of CPUs in data processing systems. With a focus on CPU introduction, factors affecting CPU performance, and CPU performance improvement strategies, such as overclocking, selection of a suitable CPU, cooling system optimization, software system optimization, and memory addition. We evaluate the advantages and disadvantages of each strategy.